Escarabajos coprófagos (Coleoptera: Scarabaeidae: Scarabaeinae) de los páramos del departamento de Nariño, Colombia (2014)
We report the presence of several dung beetle species (Coleoptera: Scarabaeidae: Scarabaeinae) in the Paramos located in Nariño, Colombia, based on the revision of museums specimens, field work and available literature. 210 specimens from three national museums and 362 individuals from collecting trips done by the Nariño University, GAICA Association and the authors were studied. A total of eight species from seven genera and 21 localities were listed. Uroxys elongatus Harold, 1868 is the species with most individuals collected or found in collections. Only one individual of Ontherus brevicollis Kirsch, 1871 and Oruscatus opalescens Bates, 1870 was found. The altitudinal range under study goes from 2800 to 3700 meters, corresponding to the highest altitude reported for U. elongatus, additionally we report the localities for two species, O. opalescens and Dichotomius monstrosus (Harold, 1875), with few or no confirmed data, increasing the knowledge for these species for Colombia.